2018
DOI: 10.1038/s41598-018-26131-y
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and ectoparasitism reduce reproductive success in an arctic-nesting top-predator

Abstract: Indirect impacts of climate change, mediated by new species interactions (including pathogens or parasites) will likely be key drivers of biodiversity reorganization. In addition, direct effects of extreme weather events remain understudied. Simultaneous investigation of the significance of ectoparasites on host populations and extreme weather events is lacking, especially in the Arctic. Here we document the consequences of recent black fly outbreaks and extreme precipitation events on the reproductive output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Similar impacts of ground ice on reindeer mortality have been reported (Hansen et al 2014). EPEs during the nesting season can significantly impact the breeding success of birds (Yannic et al 2014;Lamarre et al 2018).…”
Section: Introductionsupporting
confidence: 65%
“…Similar impacts of ground ice on reindeer mortality have been reported (Hansen et al 2014). EPEs during the nesting season can significantly impact the breeding success of birds (Yannic et al 2014;Lamarre et al 2018).…”
Section: Introductionsupporting
confidence: 65%
“…While most climate change‐related studies primarily focus on measuring the response of organisms to temperature increase, we are only starting to examine the consequences of changes in rainfall on vital rates of animals. Most results point to negative effects of rainfall on reproduction via increased risks of young mortality and foraging cost for parents (Lamarre et al, ; Öberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al, ). Despite the paucity of studies, some have already reported contrasting impacts of various climatic factors on species dynamics in various regions of the Arctic, from positive (geese: Jensen et al, ; Lecomte, Gauthier, & Giroux, ) to negative (geese: Doiron, Gauthier, & Lévesque, ; raptors: Lamarre et al, ; lemming: Ims, Henden, & Killengreen, ). At the ecosystem level, Legagneux et al () showed that warmer temperatures in the Arctic could increase predation intensity on herbivore prey.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of weather events on peregrine breeding performance has furthermore been documented in several populations, including on the Cape Peninsula, which usually exhibit reduced breeding success when experiencing high rainfall while incubating in spring and early summer [42][43][44][45][46][47][48][49]. Additionally, in the Arctic, a study showed that the increased frequency of heavy rain explained the recent decline in peregrine breeding productivity, most likely in combination with ectoparasite outbreaks [49], and demonstrated experimentally that nestling survival can be improved by the provision of nest boxes [42].…”
Section: Introductionmentioning
confidence: 99%